2009
DOI: 10.1002/cncr.24166
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent lobular neoplasia increases the risk of ipsilateral breast cancer recurrence in patients with ductal carcinoma in situ treated with breast‐conserving therapy

Abstract: BACKGROUND:Multiple clinicopathologic factors have been analyzed for their association with an increased risk of ipsilateral breast tumor recurrence (IBTR) after women receive breast‐conserving treatment (BCT) for ductal carcinoma in situ (DCIS). The reported incidence of proliferative lesions, such as atypical ductal hyperplasia (ADH), columnar cell changes (CCC), and lobular neoplasia associated with breast cancer, has been as high as 23%; however, the relevance of these lesions on the natural history of DCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…A few prior studies have assessed the presence of concomitant precursor lesions (such as atypical hyperplasia or lobular neoplasia) and LR risk [32, 33]. Rudloff et al [32] demonstrated that lobular neoplasia in the presence of DCIS was associated with an almost three-fold increase in the risk of LR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few prior studies have assessed the presence of concomitant precursor lesions (such as atypical hyperplasia or lobular neoplasia) and LR risk [32, 33]. Rudloff et al [32] demonstrated that lobular neoplasia in the presence of DCIS was associated with an almost three-fold increase in the risk of LR.…”
Section: Discussionmentioning
confidence: 99%
“…Rudloff et al [32] demonstrated that lobular neoplasia in the presence of DCIS was associated with an almost three-fold increase in the risk of LR. We also found that women in whom lobular neoplasia co-existed with DCIS had a two-fold increase in their risk of LR compared to those without concurrent lobular neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported that finding LCIS does not have an impact on the recurrence rate of patients with stage I-II carcinoma managed conservatively (35), however, two separate groups observed higher recurrence rate in patients with LCIS (36,37). Similarly, some investigators have concluded that LCIS does not affect the recurrence rate of DCIS managed conservatively, but we and others have found a twofold increase in the rate of local recurrence (38,39).…”
Section: Lobular Neoplasia and Patient Managementmentioning
confidence: 64%
“…Rudloff et al sought to determine whether the associated histologic findings of columnar cell changes, atypical ductal hyperplasia, or lobular neoplasia affected IBTR rates in patients who underwent BCS for DCIS [30]. They state that “the presence of concurrent proliferative lesions associated with in situ or infiltrating breast carcinoma may reflect underlying gene perturbations of cancer-related pathways in the uninvolved ductal epithelium, which could be markers of disease risk, occult disease, or, also, the tissue response to an existing tumor.” This study included 294 patients with DCIS treated with wide local excision, with or without radiotherapy, between 1991 and 1995, and included re-review of all available pathology slides.…”
Section: Association Of Lobular Neoplasia With Local Recurrence Ofmentioning
confidence: 99%